2017
DOI: 10.14814/phy2.13296
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal high protein intake enhances neonatal growth without significant adverse renal effects in spontaneous IUGR piglets

Abstract: In humans, early high protein (HP) intake has been recommended to prevent postnatal growth restriction and complications of intrauterine growth restriction (IUGR). However, the impact of such a strategy on the kidneys remains unknown, while significant renal hypertrophy, proteinuria, and glomerular sclerosis have been demonstrated in few experimental studies. The objective of this study was to evaluate the effects of a neonatal HP formula on renal structure in IUGR piglets. Spontaneous IUGR piglets were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The long-term renal and cardiovascular consequences of such nutritional approach are unknown. Recent experimental findings highlight short and long-term adverse renal effects of neonatal high protein diet especially in low birth weight offspring [ 51 , 52 ]. In a randomized clinical trial, the team of Lucas A has shown lower blood pressure and better insulin sensitivity in breastfed preterm born adolescent [ 53 , 54 ].…”
Section: Influence Of Perinatal and Neonatal Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term renal and cardiovascular consequences of such nutritional approach are unknown. Recent experimental findings highlight short and long-term adverse renal effects of neonatal high protein diet especially in low birth weight offspring [ 51 , 52 ]. In a randomized clinical trial, the team of Lucas A has shown lower blood pressure and better insulin sensitivity in breastfed preterm born adolescent [ 53 , 54 ].…”
Section: Influence Of Perinatal and Neonatal Conditionsmentioning
confidence: 99%
“…Moreover, various postnatal factors including nutrition and protein intake can subsequently amplify this adaptive mechanism. In low birth weight rat offspring, we and others have found out that neonatal overfeeding or high protein intake induced hypertension, proteinuria, accelerated renal insufficiency and glomerular sclerosis [ 51 , 52 , 84 , 85 ]. Nephron deficit appears as a vulnerable condition when other postnatal “hits” accelerate the development of CRD and HTN.…”
Section: Developmental Disturbancesmentioning
confidence: 99%
“…In that study, muscle samples from a sheep model of temperature-induced placental insufficiency were analysed using a bovine microarray platform, focusing mainly on differentially expressed cell cycle genes. In the present study, we undertook an unbiased genome-wide approach using RNA sequencing to identify global gene expression signatures in fetal skeletal muscle from pigs, increasingly recognized as a high value animal model of IUGR (Che et al 2010;Ebner et al 2014;Boubred et al 2017;Baek et al 2019;Gao et al 2020). In addition to numerous anatomic, metabolic and genetic similarities with humans, a distinct advantage of the pig is that comparisons between IUGR and normal weight littermates can be made, thus avoiding confounding effects of genetic background or maternal factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, in biology there are many examples in which nutritional interventions or insults in early development phases result in long-lasting changes in morphological and metabolic development. The association between early-life nutrition and health on long-term disease outcomes is described in humans (Lucas, 1991;Eriksson et al, 2003;Ness, 2004), rats (Delamaire et al, 2012), pigs (Boubred et al, 2017), and sheep (Berry et al, 2016). Hanley et al (2010) reviewed data suggesting that undernutrition in early life influences the development of metabolic and cardiovascular disease, neurodevelopment, obesity, and bone health.…”
Section: Introductionmentioning
confidence: 99%